Effects of surface energy and surface residual stresses on vibro-thermal analysis of chiral, zigzag, and armchair types of SWCNTs using refined beam theory. Issue 5 (4th May 2022) - Jena, Subrat Kumar; Chakraverty, S.; Malikan, Mohammad; Tornabene, Francesco
Abstract: In this article, vibration characteristics of three different types of Single-Walled Carbon Nanotubes (SWCNTs) such as armchair, chiral, and zigzag carbon nanotubes have been investigated considering the effects of surface energy and surface residual stresses. The nanotubes are embedded in the elastic substrate of the Winkler type and are also exposed to low and high-temperature environments. A new refined beam theory namely, one-variable shear deformation beam theory has been combined with Hamilton's principle to develop the governing equations of the proposed model. The size-dependent behavior of the SWCNTs is addressed by Eringen's nonlocal elasticity theory whereas the model is investigated analytically by employing Navier's technique. Also, a parametric study has been conducted to analyze the effects of various scaling parameters such as small scale parameter, temperature change, thermal environments, Winkler modulus, and length of the beam. The results are also validated with previously published articles in special cases witnessing robust agreement.